Answer:
![\boxed{\boxed{B.\ f(x)=15(2^2)^{\frac{x}{2}}}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cboxed%7BB.%5C%20f%28x%29%3D15%282%5E2%29%5E%7B%5Cfrac%7Bx%7D%7B2%7D%7D%7D%7D)
Step-by-step explanation:
The general equation for exponential growth is,
![y=a(1+r)^x](https://tex.z-dn.net/?f=y%3Da%281%2Br%29%5Ex)
where,
a = initial amount,
r = rate of growth,
y = future amount,
x = time.
The function
represents the growth of a frog population every year in a remote swamp.
where 15 is the initial amount of frog.
As Elizabeth wants to manipulate the formula to an equivalent form that calculates every half-year, so putting
in the general function,
![y=15(1+r)^{\frac{x}{2}}](https://tex.z-dn.net/?f=y%3D15%281%2Br%29%5E%7B%5Cfrac%7Bx%7D%7B2%7D%7D)
Now we have to find the value of r.
As we will get same future amount, irrespective to the function used, so comparing the old function with the new function,
![\Rightarrow 15(1+r)^{\frac{x}{2}}=15(2)^x](https://tex.z-dn.net/?f=%5CRightarrow%2015%281%2Br%29%5E%7B%5Cfrac%7Bx%7D%7B2%7D%7D%3D15%282%29%5Ex)
Multiplying the exponents of both sides by ![\dfrac{1}{x}](https://tex.z-dn.net/?f=%5Cdfrac%7B1%7D%7Bx%7D)
![\Rightarrow (1+r)^{\frac{x}{2}\times \frac{1}{x}}=(2)^{x\times \frac{1}{x}}](https://tex.z-dn.net/?f=%5CRightarrow%20%281%2Br%29%5E%7B%5Cfrac%7Bx%7D%7B2%7D%5Ctimes%20%5Cfrac%7B1%7D%7Bx%7D%7D%3D%282%29%5E%7Bx%5Ctimes%20%5Cfrac%7B1%7D%7Bx%7D%7D)
![\Rightarrow (1+r)^{\frac{1}{2}}=(2)^1](https://tex.z-dn.net/?f=%5CRightarrow%20%281%2Br%29%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%3D%282%29%5E1)
Squaring both sides,
![\Rightarrow (1+r)=(2)^2=4](https://tex.z-dn.net/?f=%5CRightarrow%20%281%2Br%29%3D%282%29%5E2%3D4)
![\Rightarrow r=4-1=3](https://tex.z-dn.net/?f=%5CRightarrow%20r%3D4-1%3D3)
Putting the value of r, in the general equation,
![y=15(1+3)^{\frac{x}{2}}=15(4)^{\frac{x}{2}}=15(2^2)^{\frac{x}{2}}](https://tex.z-dn.net/?f=y%3D15%281%2B3%29%5E%7B%5Cfrac%7Bx%7D%7B2%7D%7D%3D15%284%29%5E%7B%5Cfrac%7Bx%7D%7B2%7D%7D%3D15%282%5E2%29%5E%7B%5Cfrac%7Bx%7D%7B2%7D%7D)